2016
DOI: 10.1038/ejhg.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

On the reconciliation of missing heritability for genome-wide association studies

Abstract: The definition of heritability has been unique and clear, but its estimation and estimates vary across studies. Linear mixed model (LMM) and Haseman-Elston (HE) regression analyses are commonly used for estimating heritability from genome-wide association data. This study provides an analytical resolution that can be used to reconcile the differences between LMM and HE in the estimation of heritability given the genetic architecture, which is responsible for these differences. The genetic architecture was clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…If average per-SNP heritability declines in higher-LD regions, say, then the estimated heritability must fall short of the true herit- ability. This sensitivity to LD is a feature shared with the heritability-estimation method GREML (Chen, 2016; Lee & Chow, 2014; Speed, Hemani, Johnson, & Balding, 2012; Yang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…If average per-SNP heritability declines in higher-LD regions, say, then the estimated heritability must fall short of the true herit- ability. This sensitivity to LD is a feature shared with the heritability-estimation method GREML (Chen, 2016; Lee & Chow, 2014; Speed, Hemani, Johnson, & Balding, 2012; Yang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…"# $ = 0.383 ± 0.005 under HE and 0.304 ± 0.004 under REML). If REML and HE estimates are expected to converge under a classical polygenic model, the genetic architecture of a trait can bias the estimates of the two methods in different ways [33][34][35] . Previous studies 36,37 have suggested that urate concentration is a trait on the low spectrum of polygenicity and controlled by three main genes and two large effect QTLs on underlying the consistency of HE and REML estimators.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not informative about genetic architecture and has its own problem when the genetic architecture does not fit the assumptions [15], we are not suggesting that the classical method of partitioning variance components be abandoned. The classical model, and particularly the concepts of V A and h 2 , have been and will continue to be the foundation of quantitative genetics, predicting resemblance between relatives and response to selection: they inform us about the proportion of phenotypic variation that is “breedable” [3].…”
Section: Discussionmentioning
confidence: 99%